Status and advances of deep eutectic solvents for metal separation and recovery. Issue 5 (22nd February 2022) - Yuan, Ziwen; Liu, Hang; Yong, Wai Fen; She, Qianhong; Esteban, Jesús
Abstract : Deep eutectic solvents show interesting prospects as more sustainable alternatives for metal separation and recovery. Abstract : The increasing discharge of metal-associated waste not only causes growing concerns on the environment and human health but also accelerates the depletion of natural metal resources. Within this context and driven by circular economy, metal recovery is a topic of increasing research interest. Solvent extraction and leaching are commonly the major processes for metal separation and recovery from various resources. Conventional solvents used in these processes often exhibit aggressive profiles that may lead to health, environment and safety related issues as well as damage to industrial equipment. With the aim to make these separation processes safer and cleaner, it is necessary to explore the use of greener solvents. Deep eutectic solvents (DESs), a family of neoteric solvents, have emerged and attracted increasing interest in the last few years. DESs have been regarded as a type of interesting alternative to ionic liquids (ILs) owing to their ease of preparation, high biodegradability, low toxicity and high tunability. Lately, their use has started being reported for metal recovery and separation from matrices like electronic waste, minerals, biological samples, environmental samples such as soil and wastewater, food and cosmetics. This review covers a description of DESs and their properties together with the fundamentals of their use as an alternative medium to conduct metal separation from different sources. Finally, a literature survey of their application in metal detection, separation and recovery, in recent works is presented.